Cardiomyocyte NOX4 regulates resident macrophage-mediated inflammation and diastolic dysfunction in stress cardiomyopathy - Aleksandr E. Vendrov; Han Xiao; Andrey Lozhkin; Takayuki Hayami; Guomin Hu; Matthew J. Brody; Junichi Sadoshima; You-Yi Zhang; Marschall S. Runge; Nageswara R. Madamanchi (Redox Biology, 2023)
In acute sympathetic stress, catecholamine overload can lead to stress cardiomyopathy. We tested the hypothesis that cardiomyocyte NOX4 (NADPH oxidase 4)-dependent mitochondrial oxidative stress mediates inflammation and diastolic dysfunction in stress cardiomyopathy. Isoproterenol (ISO; 5 mg/kg) injection induced sympathetic stress in wild-type and cardiomyocyte (CM)-specific Nox4 knockout (Nox4CM−/−) mice. Wild-type mice treated with ISO showed higher CM NOX4 expression, H2O2 levels, inflammasome activation, and IL18, IL6, CCL2, and TNFα levels than Nox4CM−/− mice. Spectral flow cytometry and t-SNE analysis of cardiac cell suspensions showed significant increases in pro-inflammatory and pro-fibrotic embryonic-derived resident (CCR2−MHCIIhiCX3CR1hi) macrophages in wild-type mice 3 days after ISO treatment, whereas Nox4CM−/− mice had a higher proportion of embryonic-derived resident tissue-repair (CCR2−MHCIIloCX3CR1lo) macrophages. A significant increase in cardiac fibroblast activation and interstitial collagen deposition and a restrictive pattern of diastolic dysfunction with increased filling pressure was observed in wild-type hearts compared with Nox4CM−/− 7 days post-ISO. A selective NOX4 inhibitor, GKT137831, reduced myocardial mitochondrial ROS, macrophage infiltration, and fibrosis in ISO-injected wild-type mice, and preserved diastolic function. Our data suggest sympathetic overstimulation induces resident macrophage (CCR2−MHCII+) activation and myocardial inflammation, resulting in fibrosis and impaired diastolic function mediated by CM NOX4-dependent ROS.